The criminalization of stalking and characteristics of court practices in stalking cases in Lithuania - Laurinaitytė, Ilona; Michailovič, Ilona; Jarutienė, Liubovė; Zokaitė, Justina (Kriminologijos studijos, 2022)
Stalking is considered a serious public health problem as well as a harmful form of victimization often leading to severe consequences for the victim. Although there is still little agreement on the exact definition of stalking, it has been recognized that the core elements of stalking include deliberateness and recurrence of the stalker’s actions as well as victim fear and concern for safety. The main purpose of this article is to debate on the definition of stalking as well as provide the rates of stalking in Lithuania. Authors conclude that stalking refers to a constellation of a diverse range of actions and may include both direct communication with the victim and the use of cyberspace technologies. A rapid development of modern digital technologies leads to a wide variety of complex stalking behavior patterns that makes it complicated to generate an adequate legal response to this phenomenon. The results of a public survey conducted by a research group from the Law Institute of the Centre for Social Sciences in 2021 show that the rates of stalking in Lithuania are comparable to those reported in foreign studies as 17.5% of Lithuanian population have experienced stalking at least once during their lifetime. Stalking by the current or former intimate partner was the most prevalent stalking category, as it comprised nearly 39% of all stalking cases in the state. The article also covers some aspect of court practices in stalking-related cases during the period from 2016 to 2020, before anti-stalking legislation was introduced in Lithuania. By year 2021, when stalking was criminalized in Lithuania, 23 European Union member countries have managed to develop criminal anti-stalking legislation. Another aim of this article is to discuss the way criminal anti-stalking legislation was introduced in Lithuania and compare Lithuanian approach to the legal provisions enacted in other countries. Authors conclude that although the introduction of criminal anti-stalking legislation in Lithuania was an important step towards ensuring victims’ safety, it still may possibly lead to some practical issues during the criminal investigation of stalking cases.
Keywords: stalking; cyberstalking; criminalization of stalking; court practices; ntimate partner violence